The impact of unpaid work on employment status in Mexico - Franziska Dorn; Alexander Silbersdorff (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
Women in Mexico spent at least three times as much time on unpaid work compared to men. It is argued that these duties restrict women in their time use and channel them into flexible working arrangements, which are predominantly in the informal economy. This motivates the hypotheses investigated in this paper, that unpaid work impacts employment status of women in Mexico. The empirical investigations are made using the national occupation and employment survey of Mexico. The results obtained from the sequential logit model suggest that hours spend on unpaid work decrease the probability of being formally employed for women.
Keywords: 330